The law concerning the election of employees'representatives in company bodies: Report in light of the CJEU case Konrad Erzberger v TUI AG, C 566/15 - Bernhard Johann Mulder (Hans-Böckler-Stiftung, 2017)
The European Court of Justice examines the conformity of German co-determination under European law.Professor of law Bernard Johann Mulder, University of Oslo, argues that, in the case at issue, national law is not incompatible with EU law. Consequently, there is no discrimination on the grounds of nationality, and there is no obstacle to the free movement of workers.
Keywords: 330; Mitbestimmung; Europäisches Arbeitsrecht; Nationales Recht; Antidiskriminierungsrecht; Deutschland